PENGEMBANGAN MEDIA JENGA PADA LAYANAN INFORMASI UNTUK MENINGKATKAN PEMAHAMAN BAHAYA BULLYING DI MTs DDI KOTA TARAKAN - Suriata suriata; Dinda Febita Sari; Siti Rahmi (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2022)
This study aims to develop a product in the form of Jenga media on guidance and counseling information services to students at MTs DDI Tarakan City. Bullying is an act of violence or responsiveness carried out by a person or group of people with the intent and purpose to frighten. Jenga media is one of the media that can be used by guidance and counseling teachers to carry out services, especially in information services to increase understanding of the dangers of bullying so that students can understand how to deal with bullying and the bad effects of bullying behavior. This study uses a research and development approach (Research and Development). The research and development procedure uses the Borg and Gall development model, but in this study, it was carried out until the fifth stage, namely the design revision stage due to conditions during the Covid-19 pandemic. The results of material expert validation with a score of 78% indicate the appropriate category, and the validation results of design experts with a score of 89% indicate the very feasible category. This shows that the Jenga media developed is feasible and good to use in guidance and counseling information services to increase students' understanding of the risks of bullying.